The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.4196/kjpp.2012.16.2.79
|View full text |Cite
|
Sign up to set email alerts
|

Phellodendron amurenseand Its Major Alkaloid Compound, Berberine Ameliorates Scopolamine-Induced Neuronal Impairment and Memory Dysfunction in Rats

Abstract: We examine whether Phellodendron amurense (PA) and its major alkaloid compound, berberine (BER), improved memory defects caused by administering scopolamine in rats. Effects of PA and BER on the acetylcholinergic system and pro-inflammatory cytokines in the hippocampus were also investigated. Male rats were administered daily doses for 14 days of PA (100 and 200 mg/kg, i.p.) and BER (20 mg/kg, i.p.) 30 min before scopolamine injection (2 mg/kg, i.p.). Daily administration of PA and BER improved memory impairme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
62
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(65 citation statements)
references
References 45 publications
(53 reference statements)
2
62
0
1
Order By: Relevance
“…administration of scopolamine, a muscarinic cholinergic receptor antagonist, was exploited as a parmarcological model for AD in rats. Scopolamine interfere with central cholinergic functions and memory circuits, leading to decreased Ach release and subsequent memory, attention, and executive function-related deficits that are seen in aging and dementia [14]. Due to this, scopolamine-induced cognitive dysfunction is extensively used to probe potential therapeutic agents attenuating cognitive deficits [15].…”
Section: Introductionmentioning
confidence: 99%
“…administration of scopolamine, a muscarinic cholinergic receptor antagonist, was exploited as a parmarcological model for AD in rats. Scopolamine interfere with central cholinergic functions and memory circuits, leading to decreased Ach release and subsequent memory, attention, and executive function-related deficits that are seen in aging and dementia [14]. Due to this, scopolamine-induced cognitive dysfunction is extensively used to probe potential therapeutic agents attenuating cognitive deficits [15].…”
Section: Introductionmentioning
confidence: 99%
“…injection of scopolamine causes memory impairment, in accordance with previous investigations [4,18]. Scopolamine is a tropane alkaloid drug that exhibits competitive antagonism at muscarinic acetylcholine receptors (mAChRs) by interfering with cholinergic transmission in the central nervous system (CNS) [16,17]. Moreover, scopolamine administration to animals is used as an experimental model of the cognitive deterioration and memory disturbances in AD.…”
Section: Discussionmentioning
confidence: 64%
“…Scopolamine (hyoscine) is an anticholinergic drug that causes dementia by interfering with LTP. It can be used to induce memory impairment in animal models (31). It has been reported that scopolamine causes memory impairment in Morris water maze test through down regulation of protein kinase C and iNOS (32).…”
Section: Discussionmentioning
confidence: 99%